2011
DOI: 10.1074/jbc.m111.240879
|View full text |Cite
|
Sign up to set email alerts
|

Early Transcriptional Responses of HepG2-A16 Liver Cells to Infection by Plasmodium falciparum Sporozoites

Abstract: Invasion of hepatocytes by Plasmodium sporozoites deposited by Anopheles mosquitoes, and their subsequent transformation into infective merozoites is an obligatory step in the initiation of malaria. Interactions between the sporozoites and hepatocytes lead to a distinct, complex and coordinated cellular and systemic host response. Little is known about host liver cell response to sporozoite invasion, or whether it is primarily adaptive for the parasite, for the host, or for both. Our present study used gene ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 65 publications
1
13
0
Order By: Relevance
“…In addition, these claims seem to be supported by the notion that hepatocytes act as tolerizing cells [27], [28]. On the other hand, given the large number of hepatocyte genes affected by sporozoites and salivary gland components, including some related to antigen processing and presentation and chemokine production it is not far fetched to hypothesize that infected hepatocytes become full-fledged antigen presenting cells upon infection [29], [30]. This would allow the activation of T-cells specific to sporozoite and late liver stage antigens (14).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, these claims seem to be supported by the notion that hepatocytes act as tolerizing cells [27], [28]. On the other hand, given the large number of hepatocyte genes affected by sporozoites and salivary gland components, including some related to antigen processing and presentation and chemokine production it is not far fetched to hypothesize that infected hepatocytes become full-fledged antigen presenting cells upon infection [29], [30]. This would allow the activation of T-cells specific to sporozoite and late liver stage antigens (14).…”
Section: Discussionmentioning
confidence: 99%
“…Immunogenicity data from efficacy trials demonstrated that the levels of anti-CS antibodies induced in 6- to 12week-old infants were 3-fold lower than in 5- to 17-month-olds, suggesting that RTS,S/AS01 is less immunogenic in young infants 15, 23. This stage of the parasite life cycle is an attractive target for a humoral response as sporozoites can be eliminated before infecting host hepatocytes, however, this window may be as brief as 30 min 24 . The liver-stage of the P. falciparum life cycle is also a leading target for vaccination.…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, the hepatocyte constitutes far superior "raw material" compared with the RBC; hepatocytes are not only metabolically active, but also highly versatile cells, which are capable of altering uptake, storage, production, and degradation of a wide array of macromolecules in response to cellular and organismal requirements. The presence of a growing Plasmodium parasite is sensed by the host hepatocyte, which responds with activation of cellular stress responses and altered metabolism (26,27). The mammalian target of rapamycin (mTOR) kinase integrates signals from amino acids, stress, oxygen, energy, and growth factors and responds by altering cellular protein and lipid synthesis, as well as autophagy (28).…”
Section: Significancementioning
confidence: 99%